(untitled) (Research, Society and Development, 2021)
Neck pain is a musculoskeletal disease that affects a considerable number of people, causes injuries and affects their daily activities. Fascia is a kind of connective tissue, dense and uninterrupted. It involves and connects muscles, nervous structures and internal organs, and is an important element in mechanical communication between various bodily systems. Myofascial release is a technique that involves long-lasting, low-load stretching of the myofascial complex, with the aim of restoring optimal length and reducing pain to improve function. The main objective of the following review is to show the importance and relevance of the myosfascial release technique in the management of patients with neck pain. Therefore, the study is characterized as a literature review to verify the effects and benefits of myofascial release in the treatment of cervical pain, being carried out through research through the following databases: The Scientific Electronic Library Online (Scielo), Physiotherapy Evidence Database (PEDro), Latin American and Caribbean Health Sciences Literature (LILACS) and US National Library of Medicine (PubMed). Myofascial release is one of the techniques of manual therapy with low cost and easy applicability, being effective in the treatment of cervical pain, but the importance of obtaining increasingly rigorous scientific research in research aimed at the practice of physical therapy programs is necessary, in order to obtain greater efficiency and richness of content.